Consumption of steam explosion and fermentation-pretreated corn stover affects the growth performance of sheep by shifting the rumen microbiota community structure - Wang, Yong; Yin, Xuejiao; Hao, Kexing; Wang, Chao; Wei, Wurilege; Li, Yueqin; Gao, Sihui; Ji, Zeyu; Wang, Weiheng; Xie, Yuchun; Li, Changqing (Frontiers in Microbiology, 2025)
Corn stover is rich in lignocellulose, which results in low digestibility. Steam explosion is a hydrothermal pretreatment widely used to improve the digestibility of plant-based materials by inducing cell wall disruption through the rapid release of pressure. However, the impact of steam explosion-treated corn stover on the growth performance of sheep consuming it remains unclear. This study aimed to evaluate the effects of steam explosion and Lactobacillus buchneri inoculation on the nutritional value and rumen microbiota of corn stover. Corn stover was prepared with or without steam explosion and L. buchneri inoculation. Eighty sheep of similar body weight (47.62 ± 0.74 kg) were allocated into two groups and fed either untreated corn stover (CON, n = 40) or steam explosion-pretreated corn stover cocultured with L. buchneri (SEC, n = 40). The experiment lasted 60 days, and it included 10 days of adaptation and 50 days of feeding. Our results indicated that compared with the CON group, the final weight, average daily gain, and daily dry matter intake of the SEC group were significantly reduced (P < 0.05). Alpha-diversity analysis showed that the Chao1 index of the rumen microbial community tended to be lower (P < 0.1) in the SEC group. At the genus level, the SEC group had a higher (P < 0.05) relative abundance of Stylonychia, Paramecium, Treponema, Blepharisma, Neocallimastix, Stentor, Tetrahymena, Ichthyophthirius, and Pseudocohnilembus than the CON sheep. We identified the top 15 KEGG functional terms with distinct differences between the CON and SEC groups, with endocytosis being the only pathway enriched (P < 0.05) in the SEC group. Based on these findings, we speculated that, compared with the CON group, the consumption of corn stover pretreated with steam explosion and fermentation may have been associated with greater energy loss via the production of more methane and lower microbial activities, contributing to the low utilization and efficiency of this feedstuff. Before the widespread application of steam explosion to corn stover, there is a need to further optimize the production process, with particular attention paid to the proportion of corn stover in the diet.